تشابكيه قواعد تسليم المجرمين - مكائيل, تميم (Latakia University Journal - Economic and Legal Sciences Series, 2019)
قد يتخذ التعاون الدولي في مكافحة الإجرام شكلاً تشريعياً فتساهم كل دولة عن طريق تشريعها الوضعي الداخلي بإيجاد النصوص القانونية التي تكفل الوصول إلى الهدف المنشود, سواء من حيث تطبيق الصلاحية الإقليمية, أو الشخصية, أو العينية أو العالمية. مما يستتبع ذلك من حيث النتيجة, أننا قد نكون أمام جريمة معينة ارتكبت في دولة معينة و تمس دولة أو دول أخرى و الجناة يحملون جنسيات دول أخرى. بالتالي يمكن أن تتعدد و تتعارض الاختصاصات المعقودة لعدد من الدول الأخرى أو المحاكم الدولية و يغدو وراءها دولتان طالبتان للتسليم أو أكثر, أو دولة و المحكمة الجنائية الدولية, و التي قد تتقدم جميعها بطلبات تسليم إلى الدولة المطلوب إليها التسليم. إذا قد نكون أمام ورود طلبات متعددة من دول مختلفة بحق الشخص ذاته من أجل جرائم شتى, أو ورود طلبات متعددة من دول مختلفة بحق الشخص ذاته من أجل الجريمة الواحدة نفسها، و الحالة الأخرى ألا و هي ورود طلبات متعددة من دولة و من المحكمة الجنائية الدولية. فما هو الحل المتبع, هل توجد هناك أولويات أو شروط محددة, و في حال وجودها, ما هو الأساس القانوني التي تقوم علية, هل يكمن في التشريعات الداخلية, أو في الاتفاقيات الدولية. International cooperation in the fight against crime may take the form of a legislative thus contributing every state through legislation creating positive internal legal provisions that guarantee access to the desired goal, both in terms of the application of the regional authority, or personal, or in-kind or global. Which entails in terms of the result, we may be in front of a particular crime committed in a particular country and affect another State or States and the perpetrators are citizens of other countries. Thus can be multiple and inconsistent disciplinary meeting, a number of other countries or international courts and becomes behind two students or more for delivery, or the State and the International Criminal Court, and all of which have submitted applications to the delivery of the requested state. If we may be in front of the Rhode multiple requests from different countries against the same person for various crimes, or the receipt of multiple requests from different countries against the same person for one the same crime, and the other case, that is receiving multiple requests from the state and from the International Criminal Court . What is the solution practice, Are there priorities or specific conditions, and if any, what is the legal basis that it, do lies in domestic legislation, or international agreements.